1985
DOI: 10.3758/bf03207157
|View full text |Cite
|
Sign up to set email alerts
|

The category effect in visual detection and partial report

Abstract: The category effect refers to the more efficient processing of a multi-item array that can occur when some of the items are known to be from an irrelevant category, such as letters instead of digits. Previous research has found category effects in visual search, visual detection, and partialreport tasks. The present experiments investigated the category effect in a task that combined elements of both visual detection and partial report. Experiment 1 found a strong category effect when there was only one item i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…On one hand, one may regard the result as an inherent part of the interference effect; that is, the interference effect consists of a tendency to make false alarms at short SOAs. This interpretation is supported by the robustness of this pattern of results: It was found in all five of the experiments reported by Dixon (1986), as well as in Dixon (1985), Dixon and Twilley (1988), and in some of the conditions of Briand and Klein (1988). On the other hand, one might regard the false alarm increase as a separate effect from the overall decrease in accuracy.…”
supporting
confidence: 59%
“…On one hand, one may regard the result as an inherent part of the interference effect; that is, the interference effect consists of a tendency to make false alarms at short SOAs. This interpretation is supported by the robustness of this pattern of results: It was found in all five of the experiments reported by Dixon (1986), as well as in Dixon (1985), Dixon and Twilley (1988), and in some of the conditions of Briand and Klein (1988). On the other hand, one might regard the false alarm increase as a separate effect from the overall decrease in accuracy.…”
supporting
confidence: 59%
“…There was also an overall effect of SOA [F(2,22) = S2.%, p < .001], with accuracy declining as SOA increased. Previous research using this task has found a nonmonotonic effect of SOA, with accuracy being worst at SOAs of 100-200 msec and improving with longer SOAs (Di Lollo & Moscovitch, 1983;Dixon, 1985Dixon, , 1986. It is likely that such a trend would have been apparent in the present experiment as well if SOAs of 100 and 200 msec had been included.…”
Section: Methodsmentioning
confidence: 48%
“…If there was no difference between single-category displays and mixed-category displays, it would be strong evidence that the category effect was due to feature differences between letters and digits. Previous work with the category effect demonstrated that the effect is most likely to occur when there is only a single relevant item in the display (Dixon, 1985;Duncan, 1980Duncan, , 1983b. Consequently, in the mixed-eategory displays in this experiment there were six irrelevant category items (letters) and one relevant category item (a digit).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations